Response of Colombar Grapevines to Irrigation as Regards Quality Aspects and Growth - Van zyl, J.L. (South African Journal of Enology and Viticulture, 2017)
Plant response in terms of root, shoot and trunk growth as well as berry growth and composition, was determined in an irrigation trial with Colom bar comprising four soil moisture regimes, moisture stress during five phenological stages and four irrigation systems. All measurements were taken over a period of time to show parameter changes during various stages within a season. A dry 25% soil moisture regime as well as trickle irrigation improved the sugar/acid ratio by lowering the malate and total titratable acid (TT A) concentrations and by increasing the total soluble solids (TSS) compared to soil moisture regimes of 50%, 70% and 90% which showed no significant differences with regard to either juice composition or berry size. Both the 25% moisture regime and water stress during flowering and phase I of berry growth were detrimental to berry size and yielded high tartrate concentrations at veraison. Tricklers and micro-jets at a 90% soil moisture regime yielded similar curves for cumulative berry growth. Root growth studied in situ reached maxima at flowering and in the post harvest period. The 25% soil moisture regime suppressed formation of new roots. Trunk circumference measured annually was a reliable indicator of vine water stress. Daily measurements of trunk radius with the aid of dendographs showed a maximum growth rate in November as well as an une.xpected negative rate from veraison until harvesting. A programme for regulated irrigation according to the growth patterns of the various plant parts is set forth. Suppression of undesirable shoot growth without a deleterious effect on berry growth, and acquisition of a more favourable grape composition seems possible.